STRATEGI DETEKSI DINI, INTERVENSI, DAN MODEL LAYANAN KESEHATAN MENTAL PREVENTIF PADA ANAK PRASEKOLAH DI TK NURUL BAHRI - Azahra Putri Indira; Ismil Ardiana; Lailis Sa'adah; Nurin Nuzulia; Nur Salma Qotrotun Nada; Siti Mumun Muniroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Preschool children's mental health is an essential aspect that influences their social, emotional, cognitive, and behavioral development in the future. However, various emotional and mental problems in children often go undetected at an early stage, potentially hindering their growth and development. This study aims to describe the strategies for early detection, intervention, and preventive mental health service models for preschool children at TK Nurul Bahri. This research employed a qualitative approach using a case study design. The research participants consisted of the principal, teachers, and parents, who were selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings are expected to provide a comprehensive description of the implementation of early detection of children's emotional and mental conditions, the forms of intervention carried out collaboratively by teachers and parents, and the preventive mental health service model implemented by the school in collaboration with families and healthcare professionals. The results of this study are expected to serve as a reference for the development of preventive mental health services in early childhood education.